SENSITIVITY STUDY OF SURFACE-WATER MODELING SYSTEM (SMS) AS A SIMULATION TOOL OF SIDOARJO MUD DISCHARGE'S DISTRIBUTION TO KALI PORONG MODELING - TIARA DEASIANA (NIM 25505005), ALLA
The eruption of Sidoarjo's mud has been the news headlines for over 2 years. One of the concerns is the effect of Sidoarjo Mud discharge to Kali Porong. Surface-Water Modeling System (SMS) is now a common tool used in ocean engineering's world for currents and sediment distributions' modeling using finite element and finite difference method. As any other modeling systems, SMS has also some limitations. This thesis is using RMA 2 and SED2D moduls as a simulation tool of Sidoarjo Mud discharge to Kali Porong modeling, to study the limits of sediment properties and Kali Porong's current variations as the sensitivity study's parameters. The objective of this thesis is to study the limitations of Surface-Water Modeling System (SMS). This thesis also describes the distribution of Sidoarjo Mud discharge to Kali Porong Sebaran in Madura Strait. Thus, one of the public's doubts can be answered.